The USE OF COOPERATIVE LEARNING MODEL NUMBERED HEADS TOGETHER AND REALISTIC MATHEMATICS EDUCATION IN TEACHING MATHEMATICS - Ismi Widyaningrum (Cakrawala Pedagogik, 2021)
The purpose of this study was to determine the effectiveness of cooperative learning model numbered heads together and realistic mathematics education. This type of research was a Classroom Action Research. These activities were conducted in two cycles. At first cycle, learning was carried out using NHT learning model and realistic mathematics education. Then the second cycle was carried out to fix anything that wasn’t right. The results of this study were increasing the percentage of students learning, from 34,5% in Pre Cycle, to 75,86% at the end of Cycle I, and became 93,1% at the end of Cycle II. Another improvement occurred in the activities of students and teachers. All of these improvements are certainly due to the presence of improvements during the learning process carried out by teachers and researcher over the last two cycles. The conclusion of this study is that cooperative learning with Numbered Heads Together Model and Realistic Mathematics Education can improve learning achievement in teaching mathematics.